Parameters of the energy spectrum for holes in CuInSe₂ - Gorley, P.М.; Prokopenko, I.V.; Galochkinа, О.О.; Horley, P.P.; Vorobiev, Yu.V.; González-Hernández, J. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
This paper reports the coefficients Ca,b for the k-linear term in dispersion relation E(k) for holes of the upper valence bands Г⁻₆ and Г⁺₇ in p-CuInSe₂ crystals. We also obtained the tensor components for the carrier effective masses, in all three valence sub-bands of the model semiconductor. It was shown that the energy spectrum parameters for holes in CuInSe₂ allow successful explanation for the anisotropy of tensor components describing the interband light absorption coefficient and the published data for the temperature variation of the Hall coefficient, total Hall mobility and thermal voltage within the temperature range 100 K ≤ T ≤ 350 K.